Impact of Split Gate in a Novel SOI MOSFET (SPG SOI) for Reduction of Short-Channel Effects: Analytical Modeling and Simulation - Mohammad K. Anvarifard; Ali A. Orouji (Journal of Engineering)
In this paper a comprehensive investigation of a novel device called split-gate silicon-on-insulator MOSFET (SPG SOI MOSFET) is proposed to reduce short-channel effects (SCEs). Studying the device has been done by analytical approach and simulation. In the proposed structure the gate is split into two parts. A voltage difference exists between the two parts. It is demonstrated that the surface potential in the channel region exhibits a step function. Some improvements are obtained on parameters such as SCEs, hot-carrier effect (HCE), and drain-induced barrier lowering (DIBL). The accuracy of the results obtained by use of the analytical model is verified by ATLAS device simulation software. The obtained results of the model are compared with those of the single-gate (SG) SOI MOSFET. The simulation results show that the SPG SOI MOSFET performance is superior.